2014
DOI: 10.1088/0004-637x/794/1/21
|View full text |Cite
|
Sign up to set email alerts
|

A 24 Hr Global Campaign to Assess Precision Timing of the Millisecond Pulsar J1713+0747

Abstract: General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 68 publications
3
38
0
Order By: Relevance
“…Shannon & Cordes (2012) studied the pulse arrival times from a single long exposure of PSR J1713+0747, and found that this pulsarʼs single pulses showed random jitter of 26 s m  . A similar result of 27 s m  was found by Dolch et al (2014) from a more recent study using a 24 hr continuous observation of PSR J1713+0747 conducted with major telescopes around the globe. Therefore, by averaging many pulses collected in the typical ∼20 minutes NANOGrav observation, one expects 27 s 1200 m ñ = 51 ns of jitter noise.…”
Section: Noise Modelsupporting
confidence: 85%
“…Shannon & Cordes (2012) studied the pulse arrival times from a single long exposure of PSR J1713+0747, and found that this pulsarʼs single pulses showed random jitter of 26 s m  . A similar result of 27 s m  was found by Dolch et al (2014) from a more recent study using a 24 hr continuous observation of PSR J1713+0747 conducted with major telescopes around the globe. Therefore, by averaging many pulses collected in the typical ∼20 minutes NANOGrav observation, one expects 27 s 1200 m ñ = 51 ns of jitter noise.…”
Section: Noise Modelsupporting
confidence: 85%
“…The situation is likely to be significantly improved when coherent addition of the pulse signal is achieved with more telescopes, as also suggested in Dolch et al (2014). Eventually, the next generation of radio telescopes, e.g., the Square Kilometre Array and the Five hundred meter Aperture Spherical Telescope, will provide the best opportunity ever to study single pulse emission from MSPs.…”
Section: Conclusion and Discussionmentioning
confidence: 93%
“…We reanalyzed an 8 hr GBT observation from a 24 hr campaign targeting PSRJ1713+0747 (Dolch et al 2014). The increased observation length provided finer resolution but we did not see clear scintillation arcs; though, there is some notable power off the axis where conjugate time is zero.…”
Section: Changes In Flux and Scintillation Parametersmentioning
confidence: 99%